Efficacy of group therapy to reduce mental distress in women with non‐metastatic breast cancer: A systematic review and meta‐analysis of randomized controlled trials. Issue 3 (5th January 2023) - Rosendahl, Jenny; Gawlytta, Romina; Ressel, Eva; Rodeck, Johanna; Strauss, Bernhard; Mehnert‐Theuerkauf, Anja; Koranyi, Susan
Abstract: Objective: Group treatments have proven to be effective for many mental disorders and showed beneficial effects in patients with medical illness. Aim of this systematic review and meta‐analysis is to summarize the efficacy of group therapy for women with non‐metastatic breast cancer. Methods: We included studies comparing group therapy for women with non‐metastatic breast cancer to non‐active control groups, active control conditions, and individual psychotherapy. The primary outcome was mental distress, secondary outcomes were quality of life, coping, existential outcomes, fatigue, pain, and side effects. A comprehensive search was conducted in Medline, Web of Science, CENTRAL, PsycINFO, and DARE complemented by a manual search. Random‐effects meta‐analyses were run separately for different types of control groups. Results: Thirty‐seven studies (5902 patients) were included. Small effects on mental distress in favor of group treatment were found (non‐active control groups: n = 19, g = 0.42, 95% CI [0.29; 0.56], I 2 = 61.6%; active control conditions: n = 6, g = 0.20, 95% CI [0.06; 0.35], I 2 = 0%). Cognitive‐behavioral therapy (CBT) and third wave CBT group approaches proved to be most effective. Group treatments also showed beneficial effects on secondary outcomes, with most profound evidence on quality of life and coping. Conclusions: Results suggest that group interventions have the potential to reduce mental distress in women facing breast cancer. In the light of the considerable heterogeneity of most study effects, there is a need for more rigorous studies to strengthen the promising evidence and for trials examining the impact of patient and intervention characteristics on outcomes. Registration: PROSPERO international prospective register of systematic reviews, CRD42020184357.